Being LGBTQI+ in Ireland: The National Study on the Mental Health and Wellbeing of the LGBTQI+ Communities in Ireland - Keogh, Brian; Higgins, Agnes; De Vries, Jan; Downes, Carmel; Doyle, Louise; Begley, Thelma; Monahan, Mark (Trinity College Dublin, 2024)
The Being LGBTQI+ in Ireland study is a sequel to and based on the LGBTIreland study (Higgins et al. 2016) which was published in 2016 and was the largest ever study of the mental health and wellbeing of the LGBTI community in Ireland. The original study highlighted that while the majority of LGBTI participants experienced positive wellbeing, there was also a significant number who experienced mental health challenges, a significant number of young LGBTI participants who were subjected to bullying in school and issues related to harassment and safety of LGBTI people in day-to-day life. Given the many developments that have taken place since its publication, it was considered timely to track potential changes in mental health outcomes since 2016. This also offered the opportunity to gain new insights into the mental health and wellbeing of the LGBTQI+ community in Ireland by focusing on under researched areas and subgroups of the LGBTQI+ population.
PUBLISHED